Pengaruh Intellectual Capital dan Islamicity Performance Indexs Terhadap Profitability di PT Bank Muamalat Indonesia Periode 2017-2024 - Supriyanto; Fenti Yuliartin (Jurnal Perbankan Syariah, 2026)
This study aims to analyze the influence of Intellectual Capital (IC) and the Islamicity Performance Index (IPI) on Return On Assets (ROA) at Bank Muamalat Indonesia, recognized as the pioneer of Islamic banking in the country. The background of this research emphasizes the importance of intangible asset management and adherence to Islamic principles as efforts to improve financial performance in Islamic banks. This research uses a descriptive quantitative method with secondary data derived from the quarterly financial reports of Bank Muamalat Indonesia for the period 2017–2024. The data were analyzed using multiple linear regression assisted by SPSS 24 software. The results show that, partially, IC has a positive and significant effect on ROA with a significance value of 0.018, while IPI also has a positive and significant impact with a significance value of 0.003. Simultaneously, both variables significantly influence ROA, as indicated by the F-test significance value of 0.000. These findings suggest that strengthening intellectual capital and enhancing compliance with sharia principles through IPI are crucial strategies for increasing the profitability of Islamic banks.